Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Please answer this question with full working and explanation
And I reward that person with stars. ​


Please Answer This Question With Full Working And Explanation And I Reward That Person With Stars class=

Sagot :

Answer:

3 7/12

Step-by-step explanation:

First find the common denominator.

8,16,24

3,6,9,12,15,18,24

Once you find the common denominator. You have to fix the numerator.

7 2/8 would become 7 6/24

Whole numbers stay the same.

8 x 3 = 24

2 x 3 = 6

Now we repeat it on the other mixed number.

3 2/3 would become 3 16/24

Again whole numbers stay the same.

3 x 8 = 24

2 x 8 = 16

Once you convert the fractions to having the same denominator you subtract like normal.

7 6/24 - 3 16/24 = 3 14/24

3 14/24 can be simplified to 3 7/12

Answer:

[tex]\boxed{3 \dfrac{7}{12}}[/tex]

Step-by-step explanation:

The first step in simplifying the expression is to convert both the fractions into improper fractions [a/b (a > b)].

⇒ [tex]7\dfrac{2}{8} - 3\dfrac{2}{3}[/tex]

⇒ [tex]\dfrac{7 \times 8 + 2}{8} - \dfrac{3 \times 3 + 2}{3}[/tex]

⇒ [tex]\dfrac{56 + 2}{8} - \dfrac{9 + 2}{3}[/tex]

⇒ [tex]\dfrac{58}{8} - \dfrac{11}{3}[/tex]

The next step in simplifying the expression is to make the denominators of both fractions equivalent.

⇒ [tex]\dfrac{58}{8} - \dfrac{11}{3}[/tex]

⇒ [tex]\dfrac{58 \times 3}{8 \times 3} - \dfrac{11 \times 8}{3 \times 8}[/tex]

⇒ [tex]\dfrac{174}{24} - \dfrac{88}{24}[/tex]

The third step in simplifying the expression is to subtract the fractions.

⇒ [tex]\dfrac{174}{24} - \dfrac{88}{24}[/tex]

⇒ [tex]\dfrac{86}{24}[/tex]

The fourth step in simplifying the expression is to simplify the difference of the two fractions.

⇒ [tex]\dfrac{86}{24}[/tex]

⇒ [tex]\dfrac{86 \div 2}{24 \div 2}[/tex]

⇒ [tex]{\dfrac{43}{12}}[/tex]

The fifth step in simplifying the expression is to convert the improper fraction into mixed fraction.

⇒ [tex]{\dfrac{43}{12}}[/tex]

⇒ [tex]{\dfrac{36}{12}} + \dfrac{7}{12}[/tex]

⇒ [tex]3 + \dfrac{7}{12}[/tex]

⇒ [tex]\boxed{3 \dfrac{7}{12}}[/tex]